Fetomaternal outcome and effect of ursodeoxycholic acid in patients of obstetric cholestasis - Laul, Poonam; Kumari, Soma; Miglani, Urvashi; Laul, Anish; Gandhi, Shalini; Miglani, Sanjeev (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: The objective of this study was to determine fetomaternal outcome and effect of ursodeoxycholic acid in patients of obstetric cholestasis. Methods: This study was prospective observational descriptive study of 130 women, which was conducted in the department of obstetrics and gynaecology, Deen Dayal Upadhayay Hospital, New Delhi. Statistical analysis was performed using the z test when appropriate. A p value of <0.05 will be considered statistically significant. Results: Spontaneous onset of labour was present in 48.5% of patients, induction was done in 31.5% of patients and in rest 20% of patients LSCS was indicated. Normal vaginal delivery occurred in 97 of 130 patients while emergency LSCS done 33 of 130 patients. Emergency LSCS was done in 16 of 33 patients due to foetal distress. Pre-term delivery and PROM occurred in 8.5% and 9.2% of patients respectively while PPH occurred in 12.3% of patients. Among the 130 cases included in present study 34 patients (27.2%) had fetal distress, 41 patients (31.5%) had MSL and 40 neonates (32.0%) required NICU. 16 neonates out of 130 (12.8%) had birth weight below 2.5 kg. Apgar score was <7 after 5 min in 31 neonates. Conclusions: Ursodeoxycholic acid (UDCA) is useful in relieving symptoms and decreasing the biochemical markers.